THE INFLUENCE OF FUNDAMENTAL FACTORS ON STOCK PRICES AT PT GUDANG GARAM TBK - Aguswidyanti Panggarra; Dina Ramba; Jemi Pabisangan Tahirs (CV. Four Son Scholarship, 2023)
The purpose of this study is to determine the effect of fundamental factors consisting of Earning Per Share (EPS), Price Earning Ratio (PER), Dividend Payout Ratio (DPR) and Price Book Value (PBV) on stock prices at PT. Gudang Garam, Tbk in 2013-2022. The type of data used is secondary data. The data analysis technique used is the classical assumption test which consists of the normality test, multicollinearity test and heteroscedasticity test, hypothesis testing in the form of multiple linear regression analysis, partial test ( t test) and simultaneous tests (F test), as well as testing the coefficient of determination (R2). The results of this study indicate that partially the Earning Per Share (EPS) and Price Earning Ratio (PER) variables have an effect on stock prices while the Dividend Payout Ratio (DPR) and Price Book Value (PBV) variables have no effect on stock prices. Simultaneously the variables Earning Per Share (EPS), Price Earning Ratio (PER), Dividend Payout Ratio (DPR) and Price Book Value (PBV) affect stock prices. The coefficient of determination (R2) in this study is 0,847, meaning that the variables Earning Per Share (EPS), Price Earning Ratio (PER), Dividend Payout Ratio (DPR) and Price Book Value (PBV) affect the stock price by 84,7%.